Sex differences in the safety of S‐1 plus oxaliplatin and S‐1 plus cisplatin for patients with metastatic gastric cancer - Yamada, Yasuhide; Koizumi, Wasaburo; Nishikawa, Kazuhiro; Gotoh, Masahiro; Fuse, Nozomu; Sugimoto, Naotoshi; Nishina, Tomohiro; Amagai, Kenji; Chin, Keisho; Niwa, Yasumasa; Tsuji, Akihito; Imamura, Hiroshi; et al. (Cancer science, 2019)
Previous studies have shown sex‐related differences in the incidence of adverse events following treatment with fluoropyrimidines, however the mechanism of this difference is unknown. We examined sex‐related differences in the safety of S‐1 plus oxaliplatin (SOX) and S‐1 plus cisplatin (CS) in 663 metastatic gastric cancer patients taking part in a phase III study. The incidences of leukopenia (odds ratio [OR] 1.9; P = .015), neutropenia (OR 2.2; P = .002), nausea (OR 2.0; P = .009), and vomiting (OR 2.8; P < .001) were increased in women versus men treated with SOX, while vomiting (OR 2.9; P < .001) and stomatitis (OR 1.8; P = .043) were increased in women versus men treated with CS. In contrast, male patients treated with CS experienced thrombocytopenia more often (OR 0.51; P = .009). The mean relative dose intensity of S‐1 in SOX was 75.4% in women and 81.4% in men (P = .032). No difference in efficacy was observed between women and men undergoing either regimen. Sex‐related differences in adverse reactions during SOX and CS treatment were confirmed in this phase III study. Further translational research studies are warranted to pursue the cause of this difference. Sex differences in adverse reactions with oral fluoropyrimidine and oxaliplatin or cisplatin were confirmed in a phase III study; further translational research studies are warranted to pursue the causes of this outcome.